Intestinal absorptive capacity, intestinal permeability and jejunal histology in HIV and their relation to diarrhoea. Issue 5 (November 1995) - Keating, J; Bjarnason, I; Somasundaram, S; Macpherson, A; Francis, N; Price, A B; Sharpstone, D; Smithson, J; Menzies, I S; Gazzard, B G
Abstract : Intestinal function is poorly defined in patients with HIV infection. Absorptive capacity and intestinal permeability were assessed using 3-O-methyl-D-glucose, D-xylose, L-rhamnose, and lactulose in 88 HIV infected patients and the findings were correlated with the degree of immunosuppression (CD4 counts), diarrhoea, wasting, intestinal pathogen status, and histomorphometric analysis of jejunal biopsy samples. Malabsorption of 3-O-methyl-D-glucose and D-xylose was prevalent in all groups of patients with AIDS but not in asymptomatic, well patients with HIV. Malabsorption correlated significantly (r = 0.34-0.56, p < 0.005) with the degree of immune suppression and with body mass index. Increased intestinal permeability was found in all subgroups of patients. The changes in absorption-permeability were of comparable severity to those found in patients with untreated coeliac disease. Jejunal histology, however, showed only mild changes in the villus height/crypt depth ratio as compared with subtotal villus atrophy in coeliac disease. Malabsorption and increased intestinal permeability are common in AIDS patients. Malabsorption, which has nutritional implications, relates more to immune suppression than jejunal morphological changes.